Analysis of Village Budget Management in Gumukrejo Village, Pagelaran District, Pringsewu Regency - Yuliana, Yuliana; Barusman, Tina Miniawti (FKIP Universitas Lampung, 2023)
The Village Revenue and Expenditure Budget (APBDes) is a financial plan for the village government that is determined and approved by the village apparatus and the village consultative council, which is stipulated by village regulation. Gumukrejo Village's revenue is obtained through village fund revenue, tax revenue sharing and levies. The allocation of village funds and village financial assistance aims to develop and facilitate the people of Gumukrejo Village, while the Dessa Gumukrejo expenditure budget is issued for the management of village development, education and health sectors, and transportation roads. The purpose of this research is to find out how the management of the Gumukrejo Village Revenue and Expenditure Budget in Pagelaran Sub-district, Pringsewu Regency. This research uses field research methods consisting of interviews, observations, and documentation on respondents. The approach used in this research is qualitative. The result of this research is that the management of the Gumukrejo Village Budget has been carried out in a transparent and accountable manner, this is based on the role of the community who participate in the process of reporting village budgets and expenditures, laws and regulations, and government regulations. It is hoped that further researchers can provide input and ideas related to the design of village budgets.Keywords: Village Revenue, Village Expenditure, APBDes Management, Village Fund ReportingDOI: http://dx.doi.org/10.23960/E3J/v6i2.216-223